Ties and ruptures: welfare states and migration in Central and Eastern Europe - Lendvai, Noemi (San Domenico di Fiesole, 2010)
"In the last 20 years, Central Eastern Europe has witnessed a number of momentous events that have marked landmark changes in its countries’ political, social, and economic systems. Throughout the momentous changes of the last 20 years, social protection and migration issues have been and continue to be deeply intertwined, and have fundamentally shaped socio-economic and socio-political developments in the region. This paper explores the ways in which the emergent social models in Central and Eastern Europe have informed, inflicted, and imposed certain forms of migration, as well as how migration, in turn, reflects deep forms of exclusionary practices. The paper argues that migration is not simply a spontaneous process driven by market forces, but rather that social protection, welfare policies and even more broadly the ‘social’ is deeply implicated. As much as migration, or, as it is often referred to in EU discourses, ‘mobility’, brings new opportunities to Eastern European ‘free movers’, it also creates new social ruptures, new exclusions, and new divisions between those who move and those who stay."